ANALYSIS OF THE INFLUENCE OF MACROELEMENTS ON THE GROWTH AND DEVELOPMENT OF COTTON - Musurmonova Mukambar Pazitdinovna; Aspandiyorov Norbo’ta Turg’unboy o’g’li; Raimova Nasiba Sherqo’zi qizi; Ro'zmatova Sevinch Baxtiyor qizi (Journals Park Publishing, 2023)
Raw cotton is one of the main resources of our republic. Macronutrients play an important role in plant life. Nitrogen, phosphorus and potassium are among the main macronutrients and play an important role in obtaining abundant and high-quality crop yields. The effect of nitrogen and phosphorus fertilizers on the cotton yield is well studied, but little attention is paid to potash fertilizers. For this reason, the main goal is to study the effect of potash fertilizers on cotton productivity.